The Relationship between Self-Regulation and Prosocial Behavior of Fourth-Grade Elementary Students in the Digital Era - Setiawan, Ahmad Hadi; Qiftiyah, Maratul (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to examine the relationship between self-regulation and prosocial behaviour among fourth-grade primary school students in the digital age. The research method used is quantitative with a correlational approach. This study was conducted in fourth-grade primary schools, with a research population of 65 students and a research sample of 35 students determined through purposive sampling. Data were collected through questionnaire, observation, and documentation, and analyzed using Pearson's product-moment correlation formula. Normality was tested using the Shapiro-Wilk test. The results showed a significant and strong relationship between self-regulation and prosocial behaviour, with an r value of 0.771 and a significance level of 0.000 (<0.05). This indicates that higher levels of self-regulation are associated with greater prosocial tendencies among students, with self-regulation explaining 59.4% of the variation in prosocial behaviour. Theoretically, these findings reinforce the understanding of self-regulation as a critical factor influencing social-emotional competence and moral development in students. Practically, these results suggest that schools and parents implement structured self-regulation training programs and character education to encourage prosocial behaviour, especially in facing the challenges of the digital age. This study emphasizes the importance of fostering self-control and empathy to shape socially responsible and emotionally intelligent students.